Effect of Young Papaya (Carica papaya L.) Fruit Extract on Infiltration of Endometrial Inflammatory Cells of Female Rats (Rattus norvegicus) - Cecen Suci Hakameri (Science Midwifery, 2021)
Young papaya fruit is a plant thought to have anti-fertility compounds. The active compounds in young papaya fruit are thought to be able to interfere with ovarian function so that it has an impact on the normal endometrial cycle. The endometrium is the innermost lining of the uterus which is the site of implantation and development of the embryo. The aim of this study was to examine the effect of young papaya extract on the infiltration of inflammatory cells of the endometrium of female rats (Rattus norvegicus).This study uses the Post Test Only Control Group method. Total samples were 24 rats (Rattus norvegicus), 2-3 months old and 200-300 grams in weight. Samples were taken randomly, divided into 4 groups. Group (K) without being given treatment. Group (P1) was given 200 mg / 200gr BW of young papaya extract. Group (P2) was given young papaya fruit extract 400 mg / 200gr BW. Group (P3) was given young papaya fruit extract 600 mg / 200gr BW. After 20 days of treatment,the endometrial inflammatory cell infiltration was calculated. The results showed that giving young papaya fruit extract (Carica papaya L.) reduced the infiltration of endometrial inflammatory cells. The results of statistical analysis using the one way ANOVA test showed the effect of giving papaya extract on endometrial inflammatory cell infiltration (p = <0.001). It can be concluded that there is an effect of giving young papaya (Carica papaya L.) fruit extract on the infiltration of inflammatory cells in the endometrium.